Slovenska diskusija o zgodovinski povesti in zgodovinskem romanu - Hladnik, Miran (Slavistična revija, 1996)
The article presents a systematically arranged collection of critical statements concerning the historical novel and short story. These statements clearly spell out all the genre's fundamental dilemas - from the relationship between historical data and their literary treatment (i.e., the question of faithfully adhering to the facts) to skepticism about the genre's value, considering conservative form and popular nature. A special emphasis is placed on the genre's patriotic function. The rarity of comparisons with the literature attests to the autogenic concept of the genre.
Keywords: literarne študije; Slovene literature; slovenska književnost; zgodovinska povest; zgodovinski roman